The Evaluation of the Panoramic Cars Customer Satisfaction on the Papandayan Train Gambir – Garut Relation - Totok Suryono; Haniva Mulyadi; Dicky Nurfaizi Kohar (Green Publisher, 2025)
The Indonesian public. This study aims to evaluate the level of satisfaction of customers of the panoramic cars, focusing on the Panoramic cars on the Papandayan Train. The research used a quantitative SPSS approach (Statistical Package for the Social Sciences). Data was collected through literature review, direct observation, and questionnaires. The results indicate that the evaluation of customer satisfaction with the Panoramic Cars on the Papandayan Train is influenced by various factors, such as product quality, comfort, and service reliability. The research sample was taken from the regular users of the Panoramic Cars, with data analysis focusing on interpreting questionnaire results to identify factors affecting customer satisfaction. It is hoped that the findings of this study will serve as a reference for train operators in improving the quality of Panoramic cars services, as well as a reference for researchers or academics in conducting further research related to the evaluation of customer satisfaction with the Panoramic cars on the Papandayan Train.